On Virtue Ethics - Hursthouse, Rosalind (London Oxford University Press, 1999)
Virtue ethics is perhaps the most important development within late twentieth-century moral philosophy. Rosalind Hursthouse, who has made notable contributions to this development, now presents a full exposition and defence of her neo-Aristotelian version of virtue ethics. She shows how virtue ethics can provide guidance for action, illuminate moral dilemmas, and bring out the moral significance of the emotions.
Keywords: Ética